Ethylene polymers and fibers

By adjusting the synthesis conditions of ethylene polymers, an ethylene polymer with specific thermal analysis characteristics was prepared, which solved the problem of insufficient fatigue resistance, wear resistance and corrosion resistance in the marine environment, achieved high strength and high fatigue resistance, and effectively inhibited marine biological adhesion.

JP7657114B2Active Publication Date: 2025-04-04ASAHI KASEI KOGYO KABUSHIKI KAISHA
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2021121277
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-07-26
Publication Date
2025-04-04
Estimated Expiration
2041-07-26

AI Technical Summary

Technical Problem

When used in marine environments, existing ethylene polymer fibers have problems such as fatigue resistance, wear resistance and corrosion resistance, which has led to threats to marine ecosystems.

Method used

By adjusting the synthesis conditions of the ethylene polymer, an ethylene polymer with specific thermal analysis characteristics is prepared, specifically including heat treatment in step-scan DSCs, and the total content of Si and Al elements is determined by SEM-EDX analysis to ensure that it is within the specified range.

Benefits of technology

The high strength and high fatigue resistance of ethylene polymer fibers are achieved, while effectively inhibiting the adhesion and reproduction of marine organisms on the surface of ethylene polymers, improving the service life and environmental friendliness of the fibers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007657114000001
    Figure 0007657114000001
  • Figure 0007657114000002
    Figure 0007657114000002
Patent Text Reader

Abstract

To provide an ethylene polymer having excellent strength, and excellent anti-fouling property.SOLUTION: In an ethylene polymer, the ratio ΔH2 / ΔH1 of an irreversible endothermic energy amount ΔH1 of the ethylene polymer obtained by a first scan measurement of step scanning type DSC to an irreversible endothermic energy amount ΔH2 obtained by a second measurement of step scanning type DSC after annealing the ethylene polymer at 155°C for 30 min. in a step scanning apparatus, and then cooling to 50°C is 0.1 or more and less than 0.6, and the total content of Si and Al elements obtained by SEM-EDX analysis of a molded article under condition 1 and condition 2 is 1.0-6.0 mass%. (Condition 1) Three grams of the ethylene polymer is pressed at a maximum temperature of 130°C under 15 MPa for 10 min. by a press molding machine. (Condition 2) Cooling is done at 25°C for 10 min. while maintaining an average pressure of 11 MPa.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to ethylene polymers and fibers. [Background technology]

[0002] 2. Description of the Related Art Ethylene polymers have conventionally been used as raw materials for a wide variety of molded articles such as films, sheets, microporous membranes, fibers, foams, and pipes. In particular, high molecular weight ethylene polymers are suitably used as raw materials for microporous membranes for separators of secondary batteries such as lead-acid batteries and lithium ion batteries, and for high-strength fibers. The reasons why high molecular weight ethylene polymers are used for these applications include their excellent stretch processability, high tensile strength, and high chemical stability.

[0003] In particular, high strength fibers made from ultra-high molecular weight ethylene polymers are useful in applications where high loads are applied for long periods of time in harsh environments such as marine environments, as typified by ropes for mooring ships. Ship mooring ropes improved in terms of strength, creep resistance, abrasion resistance, weather resistance, etc. have been proposed (for example, see Patent Document 1). In recent years, there has been an increased demand for high strength fibers, particularly creep resistance, and various methods have been proposed for improving creep resistance (for example, see Patent Documents 2 and 3). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2015-531330 [Patent Document 2] Special Publication No. 2016-524658 [Patent Document 3] JP 2020-16007 A Summary of the Invention [Problem to be solved by the invention]

[0005] As described above, in consideration of the use of ethylene polymer fibers in severe environments such as on the ocean or in seawater, technological developments have been made to inhibit deterioration in various physical properties such as strength and durability, specifically creep resistance, abrasion resistance, weather resistance, etc.

[0006] However, in recent years, the global environment has become a problem, and we are facing damage caused by various types of environmental destruction. As a result, all products are required to have not only durability and mechanical properties that enable them to withstand long-term use, but also the ability to prevent and suppress environmental pollution and destruction. For example, from the perspective of marine environmental destruction, problems have arisen in ships transporting goods across the globe, where ballast water taken in in one area is discharged into an area with a completely different ecosystem, causing marine plant spores and plankton to be washed away and threatening the marine ecosystem. As with the problem of ballast water, ropes and other molded products with improved physical properties have been able to last longer at sea and are used in a variety of regions. However, the longer they are used, the more marine life will adhere to them, raising concerns about the destruction of underwater ecosystems and the negative impact on fishing industry through marine products. In view of such environmental problems, there is a demand for ethylene polymers with high pest control properties that can inhibit the attachment of marine organisms (organic matter (proteins), bacteria, algae, shellfish, etc.) to molded articles, and molded articles thereof.

[0007] Therefore, an object of the present invention is to provide an ethylene polymer having excellent strength and high antifouling properties capable of inhibiting adhesion of organic matter (proteins) in seawater and adhesion and proliferation of marine organisms. [Means for solving the problem]

[0008] The present inventors have conducted intensive research to solve the above-mentioned problems of the conventional techniques, and as a result have found that an ethylene polymer in which the rate of change in step scan DSC irreversible endothermic heat before and after annealing and the total content of Si and Al elements as determined by SEM-EDX analysis of a press-processed sheet are specified to fall within predetermined numerical ranges can solve the above-mentioned problems, thereby completing the present invention. That is, the present invention is as follows.

[0009] [1] An ethylene polymer having a melting endotherm ΔH of 190 J / g or more and 230 J / g or less in differential scanning calorimetry; The irreversible endothermic heat (ΔH1) of the ethylene polymer obtained by the first scan measurement of the step-scan DSC, The ethylene polymer was annealed and melted in a step-scan apparatus at 155°C for 30 minutes, cooled to 50°C, and then measured again by step-scan DSC to determine the ratio of the irreversible endothermic heat (ΔH2) to the amount of heat absorbed. (ΔH2) / (ΔH1)=0.1 or more and less than 0.6 The total content of Si and Al elements in the molded product according to the following <Condition (1)> and <Condition (2)> is 1.0 mass% or more and 6.0 mass% or less, as determined by SEM-EDX analysis. For hot forming Ethylene polymer. <Condition (1)> 3 g of the ethylene polymer is pressed in a press molding machine at a maximum temperature of 130° C. and 15 MPa for 10 minutes. <Condition (2)> Cool at 25° C. for 10 min while maintaining an average pressure of 11 MPa. [2] The viscosity average molecular weight of the polymer according to [1] above is 1 million or more and 8.5 million or less. For hot forming Ethylene polymer. 〔3〕 The molecular weight distribution (Mw / Mn) is 3.0 or more and 7.0 or less, Or [2] Described in For hot forming Ethylene polymer. 〔4〕 The above-mentioned [1] to [3] which are for fibers. 〔3〕 Any one of the following For hot formingEthylene polymer. 〔5〕 The above [1] to 〔3〕 Any one of the following For hot forming A fiber comprising an ethylene polymer. Effect of the Invention

[0010] According to the present invention, there can be provided an ethylene polymer having excellent strength and excellent antifouling properties capable of inhibiting adhesion of organic matter (proteins) in seawater and adhesion and proliferation of marine organisms. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention (hereinafter, referred to as "the present embodiment") will be described in detail. The following embodiment is an example for explaining the present invention, and is not intended to limit the present invention to the following content. The present invention can be carried out with appropriate modifications within the scope of the gist thereof.

[0012] [Ethylene polymer] The ethylene polymer of the present embodiment is The irreversible endothermic heat (ΔH1) of the ethylene polymer obtained by the first scan measurement of the step-scan DSC, The ethylene polymer is annealed and melted in a step-scan apparatus at 155°C for 30 min, cooled to 50°C, and then measured again by step-scan DSC. The ratio of the irreversible endothermic heat (ΔH2) to the irreversible endothermic heat (ΔH2) obtained by the step-scan DSC measurement is (ΔH2) / (ΔH1)=0.1 or more and less than 0.6. The combined content of Si and Al elements in the molded body according to the following <Condition (1)> and <Condition (2)> is 1.0 mass % or more and 6.0 mass % or less, as determined by SEM-EDX analysis. <Condition (1)> 3 g of the ethylene polymer is pressed in a press molding machine at a maximum temperature of 130° C. and 15 MPa for 10 minutes. <Condition (2)> Cool at 25° C. for 10 min while maintaining an average pressure of 11 MPa.

[0013] The ethylene polymer of the present embodiment has the above-mentioned structure, and thus has excellent strength and high antifouling properties that can inhibit adhesion of organic matter (proteins) in seawater and adhesion and proliferation of marine organisms.

[0014] Examples of the ethylene polymer of the present embodiment include ethylene homopolymers and copolymers of ethylene and other comonomers. The ethylene homopolymer means a polymer in which 99.5 mol % or more of the repeating units are composed of ethylene. Since the ethylene polymer is an ethylene homopolymer, it tends to be possible to draw with a high orientation and to obtain a fiber with excellent tensile strength. Furthermore, by using an ethylene polymer as a copolymer with another comonomer, side reactions during polymerization can be suppressed, the polymerization rate can be increased, and the creep properties of the resulting fiber can be improved.

[0015] Examples of other comonomers include, but are not limited to, α-olefins and vinyl compounds. The α-olefin is not particularly limited, but examples thereof include α-olefins having 3 to 20 carbon atoms, and specific examples thereof include propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, 1-nonene, 1-decene, 1-undecene, 1-dodecene, 1-tridecene, and 1-tetradecene. Among these, propylene and 1-butene are preferred from the viewpoints of heat resistance and strength of molded articles such as membranes and fibers. The comonomers may be used alone or in combination of two or more kinds.

[0016] When the ethylene polymer of the present embodiment is a copolymer of ethylene and another comonomer as described above, the molar ratio of ethylene in the copolymer is preferably 50% or more and less than 99.5%, more preferably 80% or more and less than 99.2%, and even more preferably 90% or more and less than 99%, from the viewpoint of the tensile strength of the fiber. When the ethylene polymer is a copolymer, the amount of other comonomers in the copolymer can be measured, for example, by NMR.

[0017] The ethylene polymer of the present embodiment may contain additives such as an antioxidant and a light stabilizer.

[0018] Examples of the antioxidant include, but are not limited to, phenolic compounds such as dibutylhydroxytoluene, pentaerythritol-tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], and octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate. The content of the antioxidant in the ethylene polymer of the present embodiment is not particularly limited, but is preferably 5000 ppm by mass or less, more preferably 4000 ppm by mass or less, and even more preferably 3000 ppm by mass or less.

[0019] Examples of the light resistance stabilizer include, but are not limited to, benzotriazole-based light resistance stabilizers such as 2-(5-methyl-2-hydroxyphenyl)benzotriazole and 2-(3-t-butyl-5-methyl-2-hydroxyphenyl)-5-chlorobenzotriazole; and hindered amine-based compounds such as bis(2,2,6,6-tetramethyl-4-piperidine)sebacate and poly[{6-(1,1,3,3-tetramethylbutyl)amino-1,3,5-triazine-2,4-diyl}{(2,2,6,6-tetramethyl-4-piperidyl)imino}hexamethylene{(2,2,6,6-tetramethyl-4-piperidyl)imino}]. The content of the light stabilizer in the ethylene polymer of the present embodiment is not particularly limited, but is preferably 5000 ppm by mass or less, more preferably 4000 ppm by mass or less, and further preferably 3000 ppm by mass or less.

[0020] The content of the additive in the ethylene polymer can be determined, for example, by extracting the polymer by Soxhlet extraction using tetrahydrofuran (THF) for 6 hours, and then separating and quantifying the extract by liquid chromatography.

[0021] (irreversible heat absorption amount) In the ethylene polymer of this embodiment, the ratio (ΔH2 / ΔH1) of the irreversible endothermic heat ΔH1 of the ethylene polymer obtained by the 1st scan measurement of the step-scan type DSC to the irreversible endothermic heat ΔH2 obtained by annealing and melting the ethylene polymer at 155°C for 30 min in a step-scan apparatus, cooling it to 50°C, and again measuring it with the step-scan type DSC is 0.1 or more and less than 0.6, preferably 0.15 or more and less than 0.5, and more preferably 0.18 or more and less than 0.4.

[0022] The irreversible endothermic heat of the ethylene polymer of the present embodiment is an endothermic heat determined by a step scan modulation method of a temperature modulated differential scanning calorimeter (temperature modulated DSC), and can be determined by the method described in the Examples below. During DSC temperature rise measurements, crystallization and crystal melting occur in competition with each other, so with conventional DSC measurement methods, the heat flows resulting from the formation and growth of microcrystals and melting cancel each other out, making it difficult to examine the thermal behavior of microcrystals. On the other hand, when temperature-modulated DSC is used, it is possible to separate the heat flows into irreversible components such as crystallization and reversible components such as crystal melting and glass transition, making it possible to evaluate the thermal behavior of microcrystals.

[0023] The amount of irreversible endothermic heat measured by step scanning is an index for quantifying the amount of crystals that undergo realignment and recrystallization of amorphous and molten crystalline parts through melting of crystalline parts during heating of a sample for measurement. In addition, this endothermic peak is higher than the peak temperature of heat of fusion measured by conventional DSC, and is characterized as being a crystalline component that is highly oriented and whose crystal thickness grows. The ratio (ΔH2 / ΔH1) of the irreversible endothermic heat (ΔH1) of the ethylene polymer obtained in the first scan measurement of the step-scan DSC to the second irreversible endothermic heat (ΔH2) after the ethylene polymer has been dissolved once at or above its melting point, passed through an amorphous state, and then cooled is 0.1 or more and less than 0.6, whereby the physical smoothness of the surface of a molded article using the ethylene polymer of this embodiment is improved and the amount of inorganic compounds present on the surface is increased, thereby obtaining the effect of enhancing antifouling properties against marine organisms. If the ratio (ΔH2 / ΔH1) is a high value close to 1, it is presumed that the structure has a strong configuration memory effect in which the arrangement of molecular chains does not change dramatically even after passing through an amorphous state. This means that there is little interference with other molecular chains and little entanglement in the solid higher-order structure of the ethylene polymer before it melts. On the other hand, the ratio (ΔH2 / ΔH1) is 0.1 or more and less than 0.6 In the case of , it means that the molecular chains have a moderate degree of entanglement such that the stacked state of the molecular chains before melting is released and the molecular chains are unlikely to return to the same arrangement once melted.

[0024] When the ethylene polymer of the present embodiment is hot molded, the solidification and crystallization of the molded article in the slow cooling step progresses from the outer layer to the inner center. At this time, if the molecular chains constituting the ethylene polymer are too little entangled, it is thought that the solidification of the single molecular chains proceeds independently in a state close to single crystal. Therefore, the crystalline part is formed from the outside, and at the same time, the part that becomes the amorphous part when solidified tends to gather and concentrate in the center. For this reason, if the above-mentioned irreversible endothermic heat ratio (ΔH2 / ΔH1) is greater than 0.6, the surface presence rate of inclusions other than the ethylene polymer decreases. On the other hand, if the molecular chains constituting the ethylene polymer are moderately entangled, solidification will proceed from the outside in the slow cooling process, but due to the high-order structure of the entanglement of other molecular chains with the inside, the molecular motion for external solidification will be linked to the whole, slowing down the solidification speed from the outside to the center, and the concentration of the contents in the center will also tend to be mitigated. As a result, a sufficient amount of inorganic compounds can be maintained on the surface of the molded body, and hydrophobic interactions with marine organic matter on the surface of the molded body can be suppressed, tending to improve adhesion prevention.

[0025] An example of a method for controlling the irreversible endothermic heat amounts (ΔH1, ΔH2) of the ethylene polymer of this embodiment within the above range is to adjust the synthesis conditions of the catalyst used in polymerizing the ethylene polymer. Specifically, examples of the method include using a support with a reduced content of silicon-containing components that have strong hydrophobic interactions as a polymer residue and performing a catalyst washing process to adjust the catalyst composition, and preparing a support reaction site that promotes a uniform support arrangement and catalytic activity such that neighboring polymer chains of other molecules moderately interact with each other to form a three-dimensional network during polymer growth from the catalytic active site.

[0026] (Total content of Si and Al elements measured by SEM-EDX for compact) The total Si and Al content of a molded product of the ethylene polymer of this embodiment, as determined by SEM-EDX analysis under the following <Condition (1)> and <Condition (2)>, is 1.0 mass% or more and 6.0 mass% or less, preferably 1.5 mass% or more and 5.0 mass% or less, and more preferably 2.0 mass% or more and 4.5 mass% or less. <Condition (1)> 3 g of the ethylene polymer is pressed in a press molding machine at a maximum temperature of 130° C. and 15 MPa for 10 minutes. <Condition (2)> Cool at 25° C. for 10 min while maintaining an average pressure of 11 MPa.

[0027] The total content of Si and Al elements in the molded product of the ethylene polymer of the present embodiment can be determined by the method described in the Examples below.

[0028] Since the total Si and Al content of the molded article of the ethylene polymer of this embodiment is in the range of 1.0 mass % or more and 6.0 mass % or less as described above, inorganic chemical substances that have polarity and weaken the hydrophobic interactions can be present in an appropriate dispersed state on the surface layer of the molded article having hydrophobic interactions, thereby suppressing the adhesion of organic plankton and organic matter to the surface of the molded article due to hydrophobic interactions in seawater, which can lead to the attachment of marine organisms. On the other hand, if the total content of Si and Al in the compact is more than 6.0 mass %, the inorganic substances are not uniformly dispersed on the surface layer of the compact, but are likely to accumulate as inorganic compounds and precipitate as foreign matter. This is undesirable because it causes defects in the molded body, weakens the mechanical strength, and creates physical irregularities and surface irregularities on the surface of the molded body, reducing its smoothness. This can become a starting point for the accumulation and adhesion of organic matter in the ocean.

[0029] In the ethylene polymer of the present embodiment, an example of a method for controlling the total Si and Al content of the molded article within the above numerical range is to adjust the synthesis conditions of the catalyst used when polymerizing the ethylene polymer. Specifically, examples of the method include reactively fixing MAO (methylalumoxane), which disperses uniformly in the catalyst while highly activating the catalytic activity described below, on a carrier rather than a liquid cocatalyst, or maintaining the temperature in the process at 70°C or higher by a centrifugation process.

[0030] (Viscosity average molecular weight (Mv)) The ethylene polymer of this embodiment has a viscosity average molecular weight (Mv) of preferably 1 million or more and 8.5 million or less, more preferably 2 million or more and 7 million or less, and even more preferably 3 million or more and 5 million or less. The viscosity average molecular weight (Mv) of the ethylene polymer of the present embodiment can be measured by the method described in the Examples below.

[0031] The ethylene polymer of the present embodiment has a viscosity average molecular weight (Mv) of 1,000,000 or more, and therefore can give a molded article having excellent mechanical strength such as tensile strength. On the other hand, if the viscosity average molecular weight (Mv) is higher than 8.5 million, the polymer chains become long and entangled with each other, which impairs moldability. For example, the interfacial pressure bonding between ethylene polymers in solid-state drawing processing becomes unstable, and the interfaces between ethylene polymers remain during compression processing, which tends to cause defects in the subsequent molding process or surface roughness. It is thought that the deterioration of the surface shape promotes the adhesion of organic matter and organic plankton to the surface of the molded product. Therefore, by having a viscosity average molecular weight (Mv) of 8.5 million or less, excellent moldability can be obtained, and the surface smoothness can be improved, so that adhesion of organic matter, organic plankton, etc. to the surface can be suppressed, resulting in excellent anti-fouling properties.

[0032] An example of a method for controlling the viscosity average molecular weight (Mv) of the ethylene polymer within the above range is to adjust the temperature during polymerization of ethylene. The higher the polymerization temperature, the lower the viscosity average molecular weight tends to be, and the lower the polymerization temperature, the higher the viscosity average molecular weight tends to be. Another method for adjusting the viscosity average molecular weight (Mv) to 8.5 million or less is to add a chain transfer agent such as hydrogen when polymerizing ethylene. By adding a chain transfer agent, the viscosity average molecular weight of the resulting ethylene polymer tends to be lower even at the same polymerization temperature. Furthermore, as described in US Pat. No. 6,258,903, the viscosity average molecular weight can be controlled by adding a metal complex that consumes hydrogen present in the polymerization system. It is preferable to control the viscosity average molecular weight (Mv) of the ethylene polymer of the present embodiment by combining the above methods.

[0033] (Melting endotherm ΔH in differential scanning calorimetry) The ethylene polymer of the present embodiment has a melting endotherm (ΔH) in differential scanning calorimetry of preferably 190 J / g or more and 230 J / g or less, more preferably 195 J / g or more and 225 J / g or less, and even more preferably 200 J / g or more and 220 J / g or less. The melting endotherms shown above were estimated using a Perkin Elmer Pyris1 DSC.

[0034] The ethylene polymer of the present embodiment is suitable for solid-state stretch molding, as described below. In solid-state stretching, since an ethylene polymer is formed at a temperature below its melting point, the higher-order structure of the ethylene polymer governs the moldability. That is, low entanglement between molecules is a major factor governing the moldability, and the ethylene polymer with low entanglement of molecular chains has few amorphous parts with entangled structures and many crystalline parts, that is, a high heat of fusion. This results in less entangled structures at high stretch ratios, making stretching easier. In addition, since defects are reduced, unevenness in stretching is suppressed, uniformity of mechanical strength is improved, and good moldability and high strength are realized. Therefore, according to the common sense of those skilled in the art, an ethylene polymer obtained with a single crystal structure is ultimately considered ideal. However, in the case of ethylene polymers, if the melting endotherm ΔH in differential scanning calorimetry is greater than 230 J / g, it means that the molecular chains are too little entangled and there are too few amorphous parts, which makes it easy for polymer catalyst residues to flow out during the polymerization process and to be concentrated and separated in the polymer, resulting in uneven distribution, which is not suitable for expressing antifouling properties. Therefore, from the viewpoint of achieving both excellent moldability in solid-state stretch molding and antifouling properties, the ethylene polymer of this embodiment preferably has a melting endotherm ΔH in differential scanning calorimetry of 190 J / g or more and 230 J / g or less.

[0035] In the present embodiment, examples of a method for controlling the endothermic heat of fusion (ΔH) within the above range include, in a step of preparing a catalyst described below, performing a surface treatment to increase the surface area of ​​the carrier to prepare a catalyst carrying catalytic active sites at a certain interval, and controlling the molecular chain growth rate and crystallization rate by adjusting the polymerization temperature and polymerization ethylene pressure.

[0036] (Molecular weight distribution Mw / Mn) The ethylene polymer of the present embodiment has a molecular weight distribution (Mw / Mn) of preferably 3.0 or more and 7.0 or less, more preferably 3.5 or more and 6.5 or less, and further preferably 4.0 or more and 6.0 or less. When the molecular weight distribution (Mw / Mn) is 3.0 or more, the melt fluidity during hot pressing and rolling tends to be good, and the moldability and appearance tend to be excellent. On the other hand, if the molecular weight distribution (Mw / Mn) is 7.0 or less, the proportion of low molecular weight components is suppressed, and practically sufficient strength tends to be obtained. The method for controlling the molecular weight distribution (Mw / Mn) of the ethylene polymer to the above numerical range is not particularly limited, but examples thereof include single-stage polymerization using a supported metallocene catalyst described below, etc. The molecular weight distribution of the ethylene polymer can also be controlled to the above numerical range by adjusting the polymerization temperature and the amount of the chain transfer agent.

[0037] The molecular weight distribution (Mw / Mn) of the ethylene polymer of the present embodiment is calculated based on the weight average molecular weight (Mw) and number average molecular weight (Mn) determined by gel permeation chromatography (hereinafter also referred to as "GPC"). Specifically, an orthodichlorobenzene solution in which an ethylene polymer powder is dissolved is measured by GPC, and the molecular weight distribution (Mw / Mn) can be determined based on a calibration curve prepared using commercially available monodisperse polystyrene. Specifically, it can be measured by the method described in the Examples below.

[0038] [Method for producing ethylene polymer] The ethylene polymer of the present embodiment can be produced by using ethylene, or ethylene and other monomers, and polymerizing them. Examples of the polymerization method include a method in which ethylene or a monomer containing ethylene is (co)polymerized by a suspension polymerization method or a gas phase polymerization method. Among these, the suspension polymerization method is preferred from the viewpoint of efficient removal of heat of polymerization. In the suspension polymerization method, an inert hydrocarbon medium can be used as a medium, and the α-olefin itself, which is to be the monomer, may be used as a solvent.

[0039] (Catalyst Component) In the process for producing an ethylene polymer of the present embodiment, it is preferable to use a catalyst component. As the catalyst component, for example, a metallocene catalyst, a Ziegler-Natta catalyst, etc. can be used. In particular, a metallocene catalyst is preferably used as a single-site catalyst that reduces low molecular weight components and is easy to appropriately control the molecular weight distribution.

[0040] As the metallocene catalyst, for example, a general transition metal compound is used. Such a metallocene catalyst can be obtained by supporting, on a carrier component (A), an organoaluminum compound (B), a transition metal compound having a cyclic η-bonding anionic ligand (C), and an activator (D) capable of reacting with the transition metal compound having a cyclic η-bonding anionic ligand to form a complex exhibiting catalytic activity.

[0041] The "transition metal compound (c) having a cyclic η-bonding anionic ligand" can be represented, for example, by the following formula (1). L 1 j W k M 3 X 2 p X 3 q ...(Formula 1) In the above formula 1, L 1each independently represents an η-bonding cyclic anionic ligand selected from the group consisting of a cyclopentadienyl group, an indenyl group, a tetrahydroindenyl group, a fluorenyl group, a tetrahydrofluorenyl group, and an octahydrofluorenyl group, and the ligand optionally has 1 to 8 substituents, and the substituents each independently are substituents having up to 20 non-hydrogen atoms selected from the group consisting of a hydrocarbon group having 1 to 20 carbon atoms, a halogen atom, a halogen-substituted hydrocarbon group having 1 to 12 carbon atoms, an aminohydrocarbyl group having 1 to 12 carbon atoms, a hydrocarbyloxy group having 1 to 12 carbon atoms, a dihydrocarbylamino group having 1 to 12 carbon atoms, a hydrocarbylphosphino group having 1 to 12 carbon atoms, a silyl group, an aminosilyl group, a hydrocarbyloxysilyl group having 1 to 12 carbon atoms, and a halosilyl group. In the above formula (1), M 3 is a transition metal selected from the group of transition metals belonging to Group 4 of the periodic table having a formal oxidation number of +2, +3, or +4, and has at least one ligand L 1 To 5 Represents a bound transition metal. In the formula 1, W is a divalent substituent having up to 50 non-hydrogen atoms, and L 1 and M. 3 Each bond has a valence of 1, resulting in L 1 and M 3 represents a divalent substituent that cooperates with to form a metallocycle. X 2 are each independently a monovalent anionic σ-bonded ligand; M 3 and a divalent anionic σ-bonded ligand that is divalently bonded to L 1 and M. 3 and divalent anionic σ-bonded ligands each bonded to In the above formula 1, X 3 each independently represents a neutral Lewis base coordinating compound having up to 40 non-hydrogen atoms. X 3 represents a neutral Lewis base coordinating compound. j is 1 or 2. However, when j is 2, two ligands L 1 are bonded to each other via a divalent group having up to 20 non-hydrogen atoms, and the divalent group is a group selected from the group consisting of a hydrocarbadiyl group having 1 to 20 carbon atoms, a halohydrocarbadiyl group having 1 to 12 carbon atoms, a hydrocarbyleneoxy group having 1 to 12 carbon atoms, a hydrocarbyleneamino group having 1 to 12 carbon atoms, a silanediyl group, a halosilanediyl group, and a silyleneamino group. k is 0 or 1, and p is 0, 1, or 2. 2 is a monovalent anionic σ-bonded ligand, or L 1 and M. 3 If p is a divalent anionic σ-bonded ligand bound to M 3 is an integer that is one or more smaller than the formal oxidation number of X 2 M 3 If the ligand is a divalent anionic σ-bonded ligand bound only to M, then p is M 3 is an integer that is (j+1) or more smaller than the formal oxidation number of The ligand X in the compound of formula 1 2 Examples of the alkyl group include halides, hydrocarbon groups having 1 to 60 carbon atoms, hydrocarbyloxy groups having 1 to 60 carbon atoms, hydrocarbylamide groups having 1 to 60 carbon atoms, hydrocarbyl phosphide groups having 1 to 60 carbon atoms, hydrocarbyl sulfide groups having 1 to 60 carbon atoms, silyl groups, and composite groups thereof. The neutral Lewis base coordinating compound X in the compound of formula 1 3 Examples of the alkyl group include phosphines, ethers, amines, olefins having 2 to 40 carbon atoms, dienes having 1 to 40 carbon atoms, and divalent groups derived from these compounds. The "transition metal compound (c) having a cyclic η-bonding anionic ligand" is preferably a transition metal compound represented by the above formula 1 (where j=1).

[0042] A preferred example of the compound represented by the above formula 1 (where j=1) is a compound represented by the following formula 2.

[0043] [ka]

[0044] In the above formula (2), M represents a transition metal selected from the group consisting of titanium, zirconium, and hafnium, and has a formal oxidation number of +2, +3, or +4. R 3 each independently represents a substituent having up to 20 non-hydrogen atoms selected from the group consisting of a hydrogen atom, a hydrocarbon group having 1 to 8 carbon atoms, a silyl group, a germyl group, a cyano group, a halogen atom, and a composite group thereof, provided that the substituent R 3 is a hydrocarbon group having 1 to 8 carbon atoms, a silyl group, or a germyl group, two adjacent substituents R 3 are bonded to each other to form a divalent group, whereby the two adjacent substituents R 3 can cooperate with the bonds between the two carbon atoms of the cyclopentadienyl ring to form a ring. In the formula 2, each X" independently represents a substituent having up to 20 non-hydrogen atoms selected from the group consisting of a halide, a hydrocarbon group having 1 to 20 carbon atoms, a hydrocarbyloxy group having 1 to 18 carbon atoms, a hydrocarbylamino group having 1 to 18 carbon atoms, a silyl group, a hydrocarbylamide group having 1 to 18 carbon atoms, a hydrocarbyl phosphide group having 1 to 18 carbon atoms, a hydrocarbyl sulfide group having 1 to 18 carbon atoms, and composite groups thereof. However, in some cases, two substituents X" can cooperate to form a neutral conjugated diene or a divalent group having 4 to 30 carbon atoms.

[0045] In the formula 2, Y is -O-, -S-, -NR * -OR-PR * -. However, R * represents a hydrogen atom, a hydrocarbon group having 1 to 12 carbon atoms, a hydrocarbyloxy group having 1 to 8 carbon atoms, a silyl group, a halogenated alkyl group having 1 to 8 carbon atoms, a halogenated aryl group having 6 to 20 carbon atoms, or a composite group thereof. In the formula 2, Z is SiR* 2. CR * 2. SiR * 2SiR * 2. CR * 2CR * 2. CR * =CR * , C.R. * 2SiR * 2 or GeR * 2. However, R * is as defined above and n is 1, 2 or 3.

[0046] Examples of the "transition metal compound (c) having a cyclic η-bonding anion ligand" constituting the metallocene catalyst used in the production method of the ethylene polymer of this embodiment include the compounds shown below. The zirconium compound is not particularly limited, but examples thereof include bis(methylcyclopentadienyl)zirconium dimethyl, bis(n-butylcyclopentadienyl)zirconium dimethyl, bis(indenyl)zirconium dimethyl, bis(1,3-dimethylcyclopentadienyl)zirconium dimethyl, (pentamethylcyclopentadienyl)(cyclopentadienyl)zirconium dimethyl, bis(cyclopentadienyl)zirconium dimethyl, bis(pentamethylcyclopentadienyl)zirconium dimethyl, bis(fluorenyl)zirconium dimethyl, ethylene bis(indenyl)zirconium dimethyl, ethylene bis(4,5,6,7-tetrahydro-1-indenyl)zirconium dimethyl, ethylene bis(4-methyl-1-indenyl)zirconium dimethyl, and ethylene bis(5-methyl-1-indenyl)zirconium dimethyl. dimethylsilylene(cyclopentadienyl)zirconium, and the like.

[0047] The titanium-based compound is not particularly limited, but examples thereof include [(Nt-butylamido)(tetramethyl-η5-cyclopentadienyl)-1,2-ethanediyl]titanium dimethyl, [(Nt-butylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium dimethyl, [(N-methylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium dimethyl, [(N-phenylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium dimethyl, and [(N-benzylamido)(tetramethyl-η5-cyclopentadienyl)dimethylsilane]titanium dimethyl. Examples of the dimethylsilane include titanium dimethyl, [(Nt-butylamido)(η5-cyclopentadienyl)-1,2-ethanediyl]titanium dimethyl, [(Nt-butylamido)(η5-cyclopentadienyl)dimethylsilane]titanium dimethyl, [(N-methylamido)(η5-cyclopentadienyl)-1,2-ethanediyl]titanium dimethyl, [(N-methylamido)(η5-cyclopentadienyl)dimethylsilane]titanium dimethyl, [(Nt-butylamido)(η5-indenyl)dimethylsilane]titanium dimethyl, and [(N-benzylamido)(η5-indenyl)dimethylsilane]titanium dimethyl.

[0048] The nickel-based compound is not particularly limited, but examples thereof include dibromobistriphenylphosphine nickel, dichlorobistriphenylphosphine nickel, dibromodiacetonitrile nickel, dibromodibenzonitrile nickel, dibromo(1,2-bisdiphenylphosphinoethane)nickel, dibromo(1,3-bisdiphenylphosphinopropane)nickel, dibromo(1,1'-diphenylbisphosphinoferrocene)nickel, dimethylbisdiphenylphosphine nickel, and dimethyl(1,2-bisdiphenylphosphinoethane)nickel. palladium, methyl(1,2-bisdiphenylphosphinoethane)nickel tetrafluoroborate, (2-diphenylphosphino-1-phenylethyleneoxy)phenylpyridine nickel, dichlorobistriphenylphosphine palladium, dichlorodibenzonitrile palladium, dichlorodiacetonitrile palladium, dichloro(1,2-bisdiphenylphosphinoethane)palladium, bistriphenylphosphine palladium bistetrafluoroborate, bis(2,2'-bipyridine)methyliron tetrafluoroborate etherate, and the like.

[0049] The "transition metal compound (c) having a cyclic η-bonding anion ligand" used in the production method for the ethylene polymer of this embodiment further includes a compound in which the "dimethyl" portion of the name of each of the zirconium-based compounds and titanium-based compounds described above (which appears at the end of the name of each compound, i.e., immediately after the portion "zirconium" or "titanium", and corresponds to the portion X'' in the above (Formula 2)) is replaced with "dichloro", "dibrom", "diiodine", "diethyl", "dibutyl", "diphenyl", "dibenzyl", "2-(N,N-dimethylamino)benzyl", "2-butene-1,4-diyl", "s-trans-η4-1,4-diphenyl-1,3-butadiene", "s-trans-η4-3-methyl-1,3-pentadiene", "s-trans-η4-1,4-di benzyl-1,3-butadiene", "s-trans-η4-2,4-hexadiene", "s-trans-η4-1,3-pentadiene", "s-trans-η4-1,4-ditolyl-1,3-butadiene", "s-trans-η4-1,4-bis(trimethylsilyl)-1,3-butadiene", "s-cis-η4-1,4-diphenyl-1,3-butadiene", "s-cis-η4-3-methyl- Also included are compounds with names that can be replaced with any other names, such as "s-cis-η4-1,4-pentadiene", "s-cis-η4-1,4-dibenzyl-1,3-butadiene", "s-cis-η4-2,4-hexadiene", "s-cis-η4-1,3-pentadiene", "s-cis-η4-1,4-ditolyl-1,3-butadiene", and "s-cis-η4-1,4-bis(trimethylsilyl)-1,3-butadiene".

[0050] The "transition metal compound (c) having a cyclic η-bonding anion ligand" used in the production method of the ethylene polymer of this embodiment can be synthesized by a generally known method. In the process for producing an ethylene polymer of the present embodiment, these transition metal compounds (c) may be used alone or in combination of two or more.

[0051] Next, the "activator (d) capable of reacting with a transition metal compound to form a complex exhibiting catalytic activity" (hereinafter, also simply referred to as "activator (d)") used in the production method for the ethylene polymer of the present embodiment will be described.

[0052] The activator (d) may, for example, be a compound defined by the following formula (3). [L 2 -H] d+ [M 5 m Q p ] d- ...(Formula 3) ((Formula 3), [L 2 -H] d+ represents a proton-donating Bronsted acid, where L 2 represents a neutral Lewis base, d is an integer from 1 to 7; [M 5 m Q p ] d- represents a compatible non-coordinating anion. M 5 represents a metal or metalloid belonging to any one of Groups 5 to 15 of the periodic table, and each Q is independently selected from the group consisting of hydride, halide, dihydrocarbylamide group having 2 to 20 carbon atoms, hydrocarbyloxy group having 1 to 30 carbon atoms, hydrocarbon group having 1 to 30 carbon atoms, and substituted hydrocarbon group having 1 to 40 carbon atoms. The number of Q which is a halide is 1 or less, m is an integer of 1 to 7, p is an integer of 2 to 14, d is as defined above, and pm=d.

[0053] The non-coordinating anion is not particularly limited, and examples thereof include tetrakisphenylborate, tri(p-tolyl)(phenyl)borate, tris(pentafluorophenyl)(phenyl)borate, tris(2,4-dimethylphenyl)(hydrophenyl)borate, tris(3,5-dimethylphenyl)(phenyl)borate, tris(3,5-di-trifluorimethylphenyl)(phenyl)borate, tris(pentafluorophenyl)(cyclohexyl)borate, tris(pentafluorophenyl)(naphthyl)borate, tetrakis(pentafluorophenyl)borate, triphenyl(hydroxyphenyl)borate, diphenyl-di(hydroxyphenyl)borate, triphenyl(2,4-dihydroxyphenyl)borate, tri(p-tolyl)( hydroxyphenyl)borate, tris(pentafluorophenyl)(hydroxyphenyl)borate, tris(2,4-dimethylphenyl)(hydroxyphenyl)borate, tris(3,5-dimethylphenyl)(hydroxyphenyl)borate, tris(3,5-di-trifluoromethylphenyl)(hydroxyphenyl)borate, tris(pentafluorophenyl)(2-hydroxyethyl)borate, tris(pentafluorophenyl)(4-hydroxybutyl)borate, tris(pentafluorophenyl)(4-hydroxy-cyclohexyl)borate, tris(pentafluorophenyl)(4-(4'-hydroxyphenyl)phenyl)borate, tris(pentafluorophenyl)(6-hydroxy-2-naphthyl)borate, and the like.

[0054] Other preferred non-coordinating anions include the borates listed above in which the hydroxy group is replaced with an NHR group, where R is preferably a methyl group, an ethyl group, or a tert-butyl group.

[0055] Examples of proton-donating Bronsted acids include, but are not limited to, trialkyl group-substituted ammonium cations such as triethylammonium, tripropylammonium, tri(n-butyl)ammonium, trimethylammonium, tributylammonium, and tri(n-octyl)ammonium; N,N-dialkylanilinium cations such as N,N-dimethylanilinium, N,N-diethylanilinium, N,N-2,4,6-pentamethylanilinium, and N,N-dimethylbenzylanilinium; dialkylammonium cations such as di-(i-propyl)ammonium and dicyclohexylammonium; triarylphosphonium cations such as triphenylphosphonium, tri(methylphenyl)phosphonium, and tri(dimethylphenyl)phosphonium; and dimethylsulfonium, diethylsulfonium, and diphenylsulfonium.

[0056] In the process for producing an ethylene polymer of the present embodiment, the activator (d) may be used alone or in combination of two or more kinds.

[0057] In the process for producing an ethylene polymer of this embodiment, the catalyst component is preferably supported on a carrier component (A) and used as a supported catalyst. Such a carrier component is not particularly limited, but examples thereof include at least one inorganic solid material selected from porous polymeric materials such as polyethylene, polypropylene, and styrene-divinylbenzene copolymers; inorganic solid materials of elements in Groups 2, 3, 4, 12, 13, and 14 of the Periodic Table, such as silica, zirconia, titania, boron oxide, calcium oxide, zinc oxide, barium oxide, vanadium pentoxide, chromium oxide, and thorium oxide, and mixtures thereof; and double oxides thereof. A more preferred carrier component is an inorganic solid material consisting of a magnesium compound [A] mainly composed of MgCl2.

[0058] A specific magnesium compound [A] is preferably a magnesium compound (A-3) prepared by reacting an organomagnesium compound (A-1) represented by formula (4) which is soluble in an inert hydrocarbon solvent with a chlorinating agent (A-2) represented by formula (5).

[0059] (A-1):(M 2 )γ(Mg)δ(R 8 ) e (R 9 ) f (OR 10 ) g ...(Formula 4) ((Formula 4), M 2 is a metal atom belonging to the group consisting of groups 12, 13, and 14 of the periodic table, and R 8 , R 9 and R 10 are each a hydrocarbon group having 2 to 20 carbon atoms, and γ, δ, e, f, and g are real numbers satisfying the following relationship: 0≦γ, 0<δ, 0≦e, 0≦f, 0≦g, 0 <e+f、0≦g / (γ+δ)≦2、kγ+2δ=e+f+g(ここで、kはM 2 Represents the valence of .

[0060] (A-2):H h SiCl i R 11 (4-(h+i) )...(Formula 5) (In (Equation 5), R 11 is a hydrocarbon group having 1 to 12 carbon atoms, and h and i are real numbers that satisfy the following relationship: 0 <h、0<i、0<h+i≦4)

[0061] First, the organomagnesium compound (A-1) represented by formula 4 will be described. The organomagnesium compound (A-1) is shown in the form of an organomagnesium complex compound soluble in an inert hydrocarbon solvent, but includes all dihydrocarbylmagnesium compounds and complexes of these compounds with other metal compounds. The relationship between the symbols γ, δ, e, f, and g in (Formula 4): kγ+2δ=e+f+g indicates the stoichiometry of the valence of the metal atom and the substituents.

[0062] In the formula 4, R 8 , R 9 The hydrocarbon group represented by the formula (I) is not particularly limited, but is, for example, an alkyl group, a cycloalkyl group, or an aryl group, and specific examples thereof include methyl, ethyl, propyl, butyl, propyl, hexyl, octyl, decyl, cyclohexyl, and phenyl groups. Among these, R is preferable. 8 and R 9 are each an alkyl group.

[0063] When γ>0, the metal atom M 2 As the metal atom, a metal atom belonging to the group consisting of groups 12, 13 and 14 of the periodic table can be used, for example, zinc, boron, aluminum, etc. Among these, aluminum and zinc are preferred.

[0064] In the formula (4), the metal atom M 2 The ratio δ / γ of magnesium to γ ​​is not particularly limited, but is preferably 0.1 or more and 30 or less, and more preferably 0.5 or more and 10 or less. In addition, when a certain organomagnesium compound with γ=0 is used, for example, R 8 When the alkyl group is 1-methylpropyl or the like, it is soluble in an inert hydrocarbon solvent, and such a compound is also preferable in the production method of the ethylene polymer of this embodiment.

[0065] In the above (Equation 4), R when γ=0 8 , R 9 is preferably any one of the following three groups: group (1), group (2), and group (3).

[0066] Group(1):R 8 , R 9 At least one of R is preferably a secondary or tertiary alkyl group having 4 to 6 carbon atoms, and more preferably R8 , R 9 Both have 4 to 6 carbon atoms, and at least one of them is a secondary or tertiary alkyl group. Group(2):R 8 and R 9 and R are preferably alkyl groups having different carbon numbers. 8 is an alkyl group having 2 or 3 carbon atoms, and R 9 is an alkyl group having 4 or more carbon atoms. Group(3):R 8 , R 9 It is preferable that at least one of R is a hydrocarbon group having 6 or more carbon atoms, and more preferable that R 8 , R 9 The sum of the carbon atoms contained in the alkyl group is 12 or more.

[0067] These groups are specifically shown below. In the group (1), examples of the secondary or tertiary alkyl group having 4 to 6 carbon atoms include 1-methylpropyl, 2-methylpropyl, 1,1-dimethylethyl, 2-methylbutyl, 2-ethylpropyl, 2,2-dimethylpropyl, 2-methylpentyl, 2-ethylbutyl, 2,2-dimethylbutyl, 2-methyl-2-ethylpropyl, etc. In particular, the 1-methylpropyl group is preferred.

[0068] In addition, in the group (2), examples of the alkyl group having 2 or 3 carbon atoms include ethyl, 1-methylethyl, propyl, etc. In particular, the ethyl group is preferable. The alkyl group having 4 or more carbon atoms is not particularly limited, but examples thereof include butyl, pentyl, hexyl, heptyl, octyl, etc. In particular, butyl and hexyl groups are preferred.

[0069] Furthermore, in the group (3), the hydrocarbon group having 6 or more carbon atoms is not particularly limited, but examples thereof include hexyl, heptyl, octyl, nonyl, decyl, phenyl, 2-naphthyl groups, etc. Among the hydrocarbon groups, alkyl groups are preferred, and among the alkyl groups, hexyl and octyl groups are preferred.

[0070] Generally, the more carbon atoms contained in the alkyl group, the more easily it dissolves in an inert hydrocarbon solvent, and the more the viscosity of the solution tends to increase. Therefore, it is preferable to use an alkyl group with a moderately long chain from the viewpoint of handling. The organomagnesium compound (A-1) represented by the above formula (4) is used as an inert hydrocarbon solution, but even if the solution contains or remains a trace amount of Lewis basic compounds such as ethers, esters, and amines, it can be used without any problems in practice.

[0071] Next, in the formula (4), the alkoxy group (OR 10 ) will be explained. R 10 The hydrocarbon group represented by the formula (I) is preferably an alkyl group or aryl group having 1 to 12 carbon atoms, and more preferably an alkyl group or aryl group having 3 to 10 carbon atoms. R 10 Examples of the alkyl group include, but are not limited to, methyl, ethyl, propyl, 1-methylethyl, butyl, 1-methylpropyl, 1,1-dimethylethyl, pentyl, hexyl, 2-methylpentyl, 2-ethylbutyl, 2-ethylpentyl, 2-ethylhexyl, 2-ethyl-4-methylpentyl, 2-propylheptyl, 2-ethyl-5-methyloctyl, octyl, nonyl, decyl, phenyl, naphthyl, etc. In particular, butyl, 1-methylpropyl, 2-methylpentyl, and 2-ethylhexyl groups are preferred.

[0072] The method for synthesizing the organomagnesium compound (A-1) represented by the above formula (4) is not particularly limited. For example, a method for synthesizing the organomagnesium compound (A-1) represented by the formula: R 8 MgX 1 and formula R 8 2Mg(R 8 is as described above, and X 1 is a halogen atom.) and an organomagnesium compound of the formula: M 2 R 9 k and formula: M 2 R 9(k-1) H(M 2 , R 9 and k are as described above.) in an inert hydrocarbon solvent at a temperature of 25° C. to 150° C., and optionally subsequently R 9 (R 9 is as described above. R soluble in an alcohol having a hydrocarbon group represented by 9 In another preferred method, the compound is reacted with an alkoxy magnesium compound having a hydrocarbon group represented by the following formula: and / or an alkoxy aluminum compound.

[0073] Among these, when an organomagnesium compound soluble in an inert hydrocarbon solvent is reacted with an alcohol, there is no particular restriction on the order of the reaction, and any of the following methods can be used: a method of adding the alcohol to the organomagnesium compound, a method of adding the organomagnesium compound to the alcohol, or a method of adding both simultaneously. The reaction ratio of the organomagnesium compound soluble in the inert hydrocarbon solvent and the alcohol is not particularly limited, but the molar composition ratio of alkoxy groups to all metal atoms in the alkoxy group-containing organomagnesium compound obtained as a result of the reaction, g / (γ+δ), is preferably 0≦g / (γ+δ)≦2, and more preferably 0≦g / (γ+δ)<1.

[0074] Next, the chlorinating agent (A-2) represented by the above formula (5) will be described. The chlorinating agent (A-2) is a silicon chloride compound having at least one Si-H bond, as represented by the above formula (5). (A-2):H h SiCl i R 11 (4-(h+i)) ...(Formula 5) (In (Equation 5), R 11 is a hydrocarbon group having 1 to 12 carbon atoms, and h and i are real numbers that satisfy the following relationship: 0 <h、0<i、0<h+i≦4)

[0075] In the above formula (5), R 11The hydrocarbon group represented by the formula (I) is not particularly limited, but is, for example, an aliphatic hydrocarbon group, an alicyclic hydrocarbon group, or an aromatic hydrocarbon group, and specific examples thereof include methyl, ethyl, propyl, 1-methylethyl, butyl, pentyl, hexyl, octyl, decyl, cyclohexyl, and phenyl groups. In particular, alkyl groups having 1 to 10 carbon atoms are preferred, and alkyl groups having 1 to 3 carbon atoms such as methyl, ethyl, propyl, and 1-methylethyl are more preferred. Furthermore, h and i are numbers greater than 0 that satisfy the relationship h+i≦4, and it is preferred that i is 2 or more and 3 or less.

[0076] The silicon chloride compound represented by the formula (5) is not particularly limited, but examples thereof include HSiCl3, HSiCl2CH3, HSiCl2C2H5, HSiCl2(C3H7), HSiCl2(2-C3H7), HSiCl2(C4H9), HSiCl2(C6H5), HSiCl2(4-Cl-C6H4), HSiCl2(CH=CH2), HSiCl2(CH2C6H5), HSiCl2(1-C 10 H7), HSiCl2(CH2CH=CH2), H2SiCl(CH3), H2SiCl(C2H5), HSiCl(CH3)2, HSiCl(C2H5)2, HSiCl(CH3)(2-C3H7), HSiCl(CH3)(C6H5), HSiCl(C6H5)2, etc. These compounds may be used alone or in combination of two or more. In particular, HSiCl3, HSiCl2CH3, HSiCl(CH3)2, and HSiCl2(C3H7) are preferred, with HSiCl3 and HSiCl2CH3 being more preferred.

[0077] Next, the reaction between the organomagnesium compound (A-1) represented by the above formula (4) and the silicon chloride compound (A-2) represented by the above formula (5) will be described. In the reaction, it is preferable to dilute the silicon chloride compound (A-2) with an inert hydrocarbon solvent, such as chlorinated hydrocarbons (1,2-dichloroethane, o-dichlorobenzene, dichloromethane, etc.), ether medium (diethyl ether, tetrahydrofuran, etc.), or a mixture of these. In particular, in terms of catalyst performance, an inert hydrocarbon solvent is more preferable. The reaction ratio of the organomagnesium compound (A-1) and the silicon chloride compound (A-2) is not particularly limited, but the ratio of silicon atoms contained in the silicon chloride compound (A-2) to 1 mole of magnesium atoms contained in the organomagnesium compound (A-1) is preferably 0.01 mol or more and 100 mol or less, and more preferably 0.1 mol or more and 10 mol or less.

[0078] There is no particular limitation on the method for reacting the organomagnesium compound (A-1) with the silicon chloride compound (A-2), and any of the following methods can be used: a simultaneous addition method in which the organomagnesium compound (A-1) and the silicon chloride compound (A-2) are simultaneously introduced into a reactor and reacted; a method in which (A-2) is previously charged into the reactor and then (A-1) is introduced into the reactor; or a method in which (A-1) is previously charged into the reactor and then (A-2) is introduced into the reactor. In particular, a method in which (A-2) is charged in advance into a reactor and then (A-1) is introduced into the reactor is preferred. The carrier (A-3) obtained by the above reaction is preferably separated by filtration or decantation, and then thoroughly washed with an inert hydrocarbon solvent to remove unreacted materials or by-products.

[0079] The reaction temperature between the organomagnesium compound (A-1) and the silicon chloride compound (A-2) is not particularly limited, but is preferably from 25°C to 150°C, more preferably from 30°C to 120°C, and even more preferably from 40°C to 100°C. In the simultaneous addition method in which the organomagnesium compound (A-1) and the silicon chloride compound (A-2) are simultaneously introduced into a reactor and reacted, it is preferable to adjust the temperature of the reactor to a predetermined temperature in advance, and then adjust the temperature inside the reactor to the predetermined temperature while performing the simultaneous addition, thereby adjusting the reaction temperature to the desired temperature. In the method in which the silicon chloride compound (A-2) is charged in advance into a reactor and then the organomagnesium compound (A-1) is introduced into the reactor, it is preferable to adjust the temperature of the reactor containing the silicon chloride compound (A-2) to a predetermined temperature, and then adjust the temperature inside the reactor to a predetermined temperature while introducing the organomagnesium compound (A-1) into the reactor, thereby adjusting the reaction temperature to the desired temperature. In the method of previously charging an organomagnesium compound (A-1) into a reactor and then introducing a silicon chloride compound (A-2) into the reactor, it is preferable to adjust the temperature of the reactor containing the organomagnesium compound (A-1) to a predetermined temperature, and then adjust the temperature inside the reactor to a predetermined temperature while introducing the silicon chloride compound (A-2) into the reactor, thereby adjusting the reaction temperature to the desired temperature.

[0080] The catalyst used in the process for producing an ethylene polymer of the present embodiment can be obtained by supporting, on a carrier component (A), an organoaluminum compound (B), a transition metal compound having a cyclic η-bonding anionic ligand (C), and an activator (D) capable of reacting with the transition metal compound having a cyclic η-bonding anionic ligand to form a complex exhibiting catalytic activity. The method for supporting components (B) to (D) is not particularly limited, but examples thereof include a method in which components (B), (C), and (D) are generally dissolved in an inert solvent in which they are soluble, mixed with component (A), and then the solvent is distilled off; a method in which components (B), (C), and (D) are dissolved in an inert solvent, concentrated to the extent that no solid precipitates, and then component (A) is added in an amount such that the entire amount of the concentrated liquid can be retained within the particles; a method in which components (B) and (D) are first supported on component (A), and then component (C) is supported; and a method in which components (B), (C), and (D) are successively supported on component (A). In particular, a method is preferred in which component (B) is added to carrier component (A) and then decanted after the addition, and this is repeated several times to clean and surface-treat the surface of carrier component (A) with component (B), and then components (D) and (C) are added. By washing the carrier component (A) with component (B), the specific surface area of ​​the carrier is increased and electrostatic repulsion is exerted on the carrier surface, suppressing the aggregation of carrier particles. It is believed that the Si-based components that cause hydrophobic interactions are removed to improve control, and the increase in the outer surface area of ​​the carrier disperses the distance between active points appropriately, generating appropriate entanglement during polymerization growth.

[0081] The components (c) and (d) are generally liquid or solid. The components (b), (c) and (d) may be used after diluting in an inert solvent when supported. The inert solvent used for this purpose is not particularly limited, and examples thereof include aliphatic hydrocarbons such as isobutane, pentane, hexane, heptane, octane, decane, dodecane, kerosene, etc., alicyclic hydrocarbons such as cyclopentane, cyclohexane, methylcyclopentane, etc., aromatic hydrocarbons such as benzene, toluene, xylene, etc., and mixtures thereof, etc. It is preferable to use such an inert solvent after removing impurities such as water, oxygen, sulfur, etc. using a drying agent, adsorbent, etc.

[0082] In the production process of the catalyst used in the production method of the ethylene polymer of the present embodiment, the component (B) is 1×10 in terms of Al atom per 1 g of the component (A). -5 ~1×10 -1 moles is preferred, and 1×10 -4 ~5×10 -2 Mole, component (U) is 1 x 10 -7 ~1×10 -3 moles is preferred, and 5×10 -7 ~5×10 -4 Mole, component (E) is 1 x 10 -7 ~1×10 -3 moles is preferred, and 5×10 -7 ~5×10 -4 in the molar range. The amount of each component used and the method of supporting the component are determined based on activity, economy, powder characteristics, the scale of the reactor, etc. The supported geometrically constrained metallocene catalyst obtained can be washed by a method such as decantation or filtration using an inert solvent in order to remove the organoaluminum compound, borate compound, and titanium compound that are not supported on the support. It is recommended that the above series of operations such as dissolution, contact, and washing be carried out at a temperature selected for each unit operation in the range of -30° C. to 150° C. A more preferred range of such temperatures is 0° C. to 100° C. The series of operations for obtaining a supported geometry constrained metallocene catalyst is preferably carried out in a dry inert atmosphere.

[0083] The organoaluminum compound (a) is not particularly limited, but examples thereof include trimethylaluminum, triethylaluminum, tributylaluminum, triisobutylaluminum, trihexylaluminum, trioctylaluminum, tridecylaluminum, and the like, as well as reaction products of these organoaluminum compounds with alcohols such as methyl alcohol, ethyl alcohol, butyl alcohol, pentyl alcohol, hexyl alcohol, octyl alcohol, and decyl alcohol, such as dimethylmethoxyaluminum, diethylethoxyaluminum, and dibutylbutoxyaluminum. Also preferably used are compounds consisting of alumoxanes, alkylaluminum, alkylaluminum halides, and mixtures thereof.

[0084] Alumoxanes have the overall formula: 5 )2AlO(R 5 AlO) p Al(R 5 )2 [wherein each R 5 are independently selected from the group consisting of C1-20 hydrocarbyl groups, and p is 0-50, preferably, R5 is a C1-4 group and p is 5-30. Methylalumoxane (or "MAO"), in which most of the R groups in the mixture of compounds are methyl, is the preferred alumoxane. Alumoxanes are also readily available commercial products, typically as solutions in hydrocarbon solvents.

[0085] The polymerization method for the ethylene polymer of the present embodiment may be, for example, a suspension polymerization method or a gas phase polymerization method. Among these, the suspension polymerization method is preferred from the viewpoint of efficient removal of heat of polymerization. In the suspension polymerization method, an inert hydrocarbon medium can be used as the medium, and the α-olefin itself, which is to become the monomer, may be used as the solvent.

[0086] Examples of inert hydrocarbon media include, but are not limited to, aliphatic hydrocarbons such as propane, butane, isobutane, pentane, isopentane, hexane, heptane, octane, decane, dodecane, and kerosene; alicyclic hydrocarbons such as cyclopentane, cyclohexane, and methylcyclopentane; aromatic hydrocarbons such as benzene, toluene, and xylene; halogenated hydrocarbons such as ethylene chloride, chlorobenzene, and dichloromethane; and mixtures thereof.

[0087] The polymerization temperature is not particularly limited, but is preferably 20° C. or higher and 70° C. or lower, more preferably 25° C. or higher and 60° C. or lower, and even more preferably 30° C. or higher and 50° C. or lower. A polymerization temperature of 20° C. or higher tends to enable industrially efficient production. Also, a polymerization temperature of 70° C. or lower tends to enable continuous and stable operation with low entanglement suppressed by suppressing the growth rate.

[0088] The polymerization pressure is not particularly limited, but from the viewpoint of the average particle size of the ethylene polymer, it is preferably from 0.1 MPa to 2.0 MPa, more preferably from 0.1 MPa to 1.5 MPa, and even more preferably from 0.1 MPa to 1.0 MPa.

[0089] The polymerization reaction can be carried out in any of a batch system, a semi-continuous system, and a continuous system, but a continuous system is preferred. By carrying out the polymerization in a continuous manner, ethylene gas, a solvent, a catalyst, etc. are continuously supplied to the polymerization system and continuously discharged together with the produced ethylene (co)polymer, which makes it possible to suppress a localized high temperature state caused by a sudden reaction of ethylene, and the polymerization system tends to become more stable.

[0090] By adding hydrogen as a chain transfer agent in an appropriate concentration to the polymerization system, the molecular weight tends to be controlled within an appropriate range. By adding hydrogen to the polymerization system, in addition to controlling the molecular weight, it tends to be possible to promote the chain transfer of the catalyst and suppress the polymerization growth, which tends to suppress the rapid growth of polymer chains and prevent the generation of irregular particles. The hydrogen molar fraction in the gas phase within the polymerization system is preferably 0 mol % to 3.0 mol %, more preferably 0.5 mol % to 2.5 mol %, and even more preferably 1.0 mol % to 2.0 mol %, based on the entire system.

[0091] It is more preferable that hydrogen is brought into contact with the catalyst in advance and then added to the polymerization system through a catalyst introduction line. Immediately after the catalyst is introduced into the polymerization system, the catalyst concentration near the outlet of the introduction line is high, and the rapid reaction of ethylene increases the possibility of localized high temperature conditions. Here, by contacting hydrogen with the catalyst before introducing it into the polymerization system, it is possible to suppress the initial activity of the catalyst, suppress the production of ethylene polymers that have reached a high temperature due to rapid polymerization, and enable stable reaction growth in molecular chain growth, with a tendency for entanglement to become uniform.

[0092] The solvent separation method can be carried out by decantation, centrifugation, filter filtration, etc., but centrifugation is more preferred because it has good separation efficiency between the ethylene polymer and the solvent. In addition to the inert gas in the centrifuge, steam can also be supplied to deactivate the catalyst. The temperature inside the centrifugation process is not particularly limited, but is preferably 65°C to 90°C, more preferably 68°C to 85°C, and even more preferably 70°C to 80°C. In the deactivation step of the catalyst used to synthesize the ethylene polymer, metals and inorganic components contained in the ethylene polymer are separated together with the solvent to the outside of the polymer. In order to prevent the residual material from leaking out while deactivating the catalyst in the centrifugation step, it is effective to gasify the solvent and separate it. By centrifuging the residual solvent at a high temperature above the boiling point, the low molecular weight components remaining in the solvent are reduced, and the polar compounds tend to be efficiently separated so that they remain in the polymer.

[0093] The catalyst deactivator is not particularly limited, but examples thereof include oxygen, water, alcohols, glycols, phenols, carbon monoxide, carbon dioxide, ethers, carbonyl compounds, and alkynes.

[0094] The drying temperature after the separation of the solvent is not particularly limited, but from the viewpoint of controlling the surface area of ​​the ethylene polymer, it is preferably 60° C. or more and 150° C. or less, more preferably 70° C. or more and 140° C. or less, and even more preferably 80° C. or more and 130° C. or less. A drying temperature of 60° C. or more tends to enable efficient drying. Furthermore, a drying temperature of 150° C. or less tends to enable drying in a state in which decomposition and crosslinking of the ethylene polymer are suppressed, and the particles tend to be prevented from being exposed to an ambient environment above the melting point of the ethylene polymer and to be prevented from partially melting.

[0095] [Molded body] The ethylene polymer of the present embodiment can be molded to obtain a molded article. The molded article can be obtained by, for example, injection molding, extrusion molding, press molding, etc. Even if the molecular weight of the polyethylene makes it difficult to melt mold the polyethylene alone, the polymer can be gelled with a solvent or the like to obtain a molded article by various general molding methods.

[0096] [Application] The ethylene polymer of the present embodiment has good processability in solid-state drawing processing. The ethylene polymer of the present embodiment is suitable for use as fibers, for example, ropes, nets, fishing lines, gloves, fabrics, bulletproof vests, bulletproof covers for armored vehicles, laminates, sporting goods, sutures, and the like. In particular, its use in the ocean is preferable, and due to its functionality of suppressing environmental pollution, it can be suitably used as ship mooring ropes, yacht ropes, fishing lines, and fishing nets. EXAMPLES

[0097] The present embodiment will be described in more detail below with reference to specific examples and comparative examples, but the present invention is not limited to these examples and comparative examples. In the examples and comparative examples described later, various physical properties and evaluations were performed by the methods described below.

[0098] [Irreversible heat absorption by step-scan measurement] The measurement sample used was an ethylene polymer powder that had been stored after polymerization under constant temperature and humidity conditions of 23° C. and 60% humidity. Measurements were performed using a PerkinElmer DSC (DSC8500) in step scan measurement mode (sample mass: 8 mg, sample pan material: aluminum, measurement temperature: 50 to 200°C, heating rate: 10°C / min, heating step width: 1°C, isothermal time: 2 min). An empty aluminum sample pan was also measured under the same conditions, and the temperature-heat flow curve was corrected using the data analysis application Pyris. The amount of irreversible heat absorption in the corrected temperature-heat flow curve was calculated. The irreversible endothermic heat (ΔH1) of the ethylene polymer obtained by the 1st scan measurement of the step-scan DSC and the irreversible endothermic heat (ΔH2) obtained by annealing and melting the ethylene polymer in a step-scan apparatus at 155°C for 30 min, cooling it to 50°C, and measuring it again by the step-scan DSC were measured, and the ratio thereof: (ΔH2) / (ΔH1) was calculated.

[0099] [Total content of Si and Al elements in pressed compacts measured by SEM-EDX] Test pieces obtained by press-molding ethylene polymers were used as samples, and the amounts of Si and Al in the test pieces were measured using a tabletop electron microscope TM3030 manufactured by Hitachi High-Technologies Corporation and an energy dispersive X-ray analyzer (EDX) SwiftED3000 manufactured by OXFORD INSTRUMENTS. Three grams of an ethylene polymer was filled into a circular mold having a diameter of 52 mm and a thickness of 1.5 mm, and pressed for 10 minutes at a maximum temperature of 130°C and an average pressure of 15 MPa using a press molding machine. Thereafter, the molded product was cooled at 25°C for 10 minutes while maintaining the pressure at 11 MPa to obtain a circular molded product, which was used as a test specimen. Observations were made with the TM3030 in normal mode, an accelerating voltage of 15 kV, and a magnification of 300x, and the position was adjusted so that the entire surface of the test piece was visible on the observation screen. Under the above observation conditions, images were captured using Swift3000, and 30 arbitrary points were observed in point mode in Point & ID observation mode (high sensitivity process time, collection time 30 seconds), and the total content of Si and Al elements was calculated.

[0100] [Viscosity average molecular weight (Mv)] Using an ethylene polymer as a sample, the viscosity average molecular weight (Mv) of the ethylene polymer was determined by the method shown below in accordance with ISO1628-3 (2010). First, 20 mg of ethylene polymer was weighed into a melting tube, and the melting tube was replaced with nitrogen. Then, 20 mL of decahydronaphthalene (containing 1 g / L of 2,6-di-t-butyl-4-methylphenol) was added, and the mixture was stirred at 150°C for 2 hours to dissolve the ethylene powder. The solution was placed in a thermostatic bath at 135°C and measured for the fall time between the marked lines (t s Similarly, for samples in which the amount of ethylene polymer was changed to 10 mg, 5 mg, and 2 mg, the falling time between the marked lines (t s ) was measured. As a blank, the falling time (t b ) was measured. The reduced viscosity (η sp / C) are plotted, and the concentration (C) (unit: g / dL) and reduced viscosity (η sp / C), and the intrinsic viscosity ([η]) extrapolated to a concentration of zero was calculated. η sp / C=(t s / t b -1) / 0.1: (unit: dL / g) Next, the viscosity average molecular weight (Mv) was calculated using the above-mentioned value of the intrinsic viscosity [η] in the following formula. Mv = (5.34 × 10 4 )×[η] 1.49

[0101] [Mw / Mn] A sample solution was prepared by adding 15 mL of o-dichlorobenzene to 20 mg of ethylene polymer and stirring at 150° C. for 1 hour, and then measuring by gel permeation chromatography (GPC). Separately, the Mw of a commercially available standard polystyrene was multiplied by a coefficient of 0.43 to obtain a polyethylene-equivalent molecular weight, and a primary calibration line was created from a plot of elution time versus polyethylene-equivalent molecular weight. Based on the GPC measurement results and the above calibration curve, the number average molecular weight (Mn), weight average molecular weight (Mw), and molecular weight distribution (Mw / Mn) were determined. The apparatus and conditions used for the measurement are as follows: Apparatus: Waters 150-C ALC / GPC Detector: RI detector Mobile phase: o-dichlorobenzene (for high performance liquid chromatography) Flow rate: 1.0mL / min Column: One AT-807S column manufactured by Showa Denko KK and two TSK-gel GMH-H6 columns manufactured by Tosoh Corporation were connected together. Column temperature: 140℃

[0102] [Melting endotherm (ΔH) by differential scanning calorimetry (DSC)] The melting endotherm ΔH of the ethylene polymer was measured using a Perkin Elmer Pyris1 DSC as a differential scanning calorimeter (DSC). The measurement sample was weighed out to 8.3-8.5 g on an electronic balance and placed in an aluminum sample pan. An aluminum cover was attached to this pan and placed in a differential scanning calorimeter. While purging with nitrogen at a flow rate of 20 mL / min, the sample and reference sample were held at 50°C for 1 minute, then heated from 50°C to 180°C at a heating rate of 10°C / min, held at 180°C for 5 minutes, and then cooled to 50°C at a cooling rate of 10°C / min. The baseline of the temperature-rising DSC curve obtained at this time was corrected, and the peak area was calculated using the analysis software Pyris software (version 7), and the measured heat of fusion (ΔH) was derived by dividing it by the sample mass.

[0103] [Evaluation method] (Tensile strength of solid-phase stretched molded product) 3 grams of ethylene polymer was pressed for 10 minutes at a maximum temperature of 126°C and an average pressure of 11 MPa using a press molding machine, and then cooled at 25°C for 10 minutes while maintaining the average pressure of 11 MPa to obtain a pressed sheet. The obtained press sheet was preheated at 140° C. and rolled at 130° C. with a rolling mill having a roll delivery speed of 1 m / min to a stretch ratio of 6 times to obtain a sheet. The sheet obtained by the rolling process was cut out and set in a tensile testing machine (INSTRON Corporation, INSTRON5564) with a chuck distance of 15 mm. It was then subjected to two consecutive stretching processes in the same direction as the roll rolling at 130°C and a stretching speed of 30 mm / min, obtaining a solid-state stretched molded product with a stretch ratio of 200 times from the pressed sheet. The total stretch ratio was determined by the mass per unit length of the film before and after stretching. The tensile strength (breaking strength) (unit: GPa) was calculated from the stress and elongation at the breaking point when stretched using the above tensile tester under conditions of a test temperature of 20° C. and a tensile speed of 50 mm / min.

[0104] [Thickness Unevenness of Solid-Phase Stretched Product] 3 grams of ethylene polymer was pressed for 10 minutes at a maximum temperature of 126°C and an average pressure of 11 MPa using a press molding machine, and then cooled at 25°C for 10 minutes while maintaining the average pressure of 11 MPa to obtain a pressed sheet. The obtained press sheet was preheated at 140° C. and rolled at 130° C. with a rolling mill having a roll delivery speed of 1 m / min to a stretch ratio of 6 times to obtain a sheet. The sheet obtained by the rolling process was cut out and set in a tensile testing machine (INSTRON Corporation, INSTRON5564) with a chuck distance of 15 mm. Roll rolling was performed at 130°C and a stretching speed of 50 mm / min, and a solid stretched molded product with a stretch ratio of 36 times was obtained from the pressed sheet. The thickness of the test piece of this molded body was measured in the stretching direction at 20 points in the center, and the unevenness in thickness was evaluated according to the following evaluation criteria. <Evaluation criteria> Thickness variation coefficient: less than 2% Thickness variation coefficient: 2% to 5% Thickness variation coefficient: over 5% ×

[0105] [Evaluation of static antifouling properties by immersion in actual seawater] The ethylene polymer was hot-pressed in a 4.0 mm thick mold using a press molding machine manufactured by Toyo Seiki Co., Ltd. under conditions of a temperature of 200° C. and an average pressure of 5 MPa for 5 minutes, followed by 15 MPa for 10 minutes, and then cooled and pressed at 25° C. for 10 minutes while maintaining the average pressure at 11 MPa. The surface of a punched sample of 100 mm x 40 mm was washed with hexane and then sterilized with ethanol. The sterilized sample was attached to a stainless steel sample stand using a tie lock to secure it against wavering caused by ocean waves. The samples were hung from a nylon net on a raft installed in Mizushima Port (Kurashiki City, Okayama Prefecture) at the Mizushima Manufacturing Plant C Area of ​​Asahi Kasei Corporation, so that the samples were 1.5 m below the water surface and facing south. The samples were left to soak for four months starting in February 2019. They were then collected and dried at 80°C for 24 hours. After drying, the area [%] of the adhered slime (diatom coating) was measured and evaluated according to the following criteria. <Evaluation criteria for slime adhesion area> Slime adhesion area is between 0% and 3%...◎ Slime adhesion area is 3% or more but less than 8%... Slime adhesion area is 8% or more... ×

[0106] [Production Example 1] (Solid catalyst component [A]) (1) Synthesis of raw material (a-1) In an 8L stainless steel autoclave that had been thoroughly purged with nitrogen, 1 mol / L of Mg6(C4H9) 12 2,000mL of Al(C2H5)3 hexane solution (equivalent to 2000mmol of magnesium and aluminum) was charged, and 146mL of 5.47mol / L n-butanol hexane solution was dropped over 3 hours while stirring at 50℃, and the line was washed with 300mL of hexane after completion. Stirring was continued for another 2 hours at 50℃. After the reaction was completed, the mixture was cooled to room temperature and used as raw material (a-1). The magnesium concentration of raw material (a-1) was 0.704mol / L.

[0107] (2) Synthesis of magnesium-containing support (A-1) 1,000mL of 1mol / L hydroxytrichlorosilane hexane solution was charged into an 8L stainless steel autoclave that had been thoroughly purged with nitrogen, and 1,340mL of the hexane solution of the organic magnesium compound (a-1) (equivalent to 943mmol of magnesium) was added dropwise over 5 hours at 65°C, and the reaction was continued for another 1 hour at 60°C with stirring. After the reaction was completed, the supernatant was removed and the mixture was washed four times with 1,800mL of hexane to obtain (A-1) carrier. Analysis of this carrier revealed that it contained 8.1mmol of magnesium per 1g of solid.

[0108] (3) Carrier surface treatment with aluminum compounds (A-3) 13 mL of a 1.04 g / L hexane slurry of the (A-1) carrier and 1.2 mL of MMAO-3A / hex (modified methylalumoxane, Al content 5.7 mass% hexane solution MMAO manufactured by Tosoh Finechem Corporation) were stirred at 450 rpm at 25 °C for 1 hour. The resulting slurry was thoroughly washed with hexane until the supernatant was clear, to obtain the (A-3) carrier.

[0109] (4) Synthesis of raw material (a-2) [(Nt-butylamido)(tetramethyl-η 5 200 mmol of [(-cyclopentadienyl)dimethylsilane]titanium-1,3-pentadiene (hereinafter referred to as "titanium complex") was dissolved in 1250 mL of Isopar E [a trade name for a hydrocarbon mixture manufactured by Exxon Chemical Company (USA)], 40 mL of a 1 mol / L hexane solution of commercially available butylethylmagnesium was added, and further hexane was added to adjust the titanium complex concentration to 80 mmol / L, thereby obtaining raw material (a-2).

[0110] (5) Synthesis of raw material (a-3) 5.7 g of bis(hydrogenated tallow alkyl)methylammonium-tris(pentafluorophenyl)(4-hydroxyphenyl)borate (hereinafter referred to as "borate") was added and dissolved in 50 mL of toluene to obtain a 100 mmol / L toluene solution of borate. 5 mL of a 1 mol / L hexane solution of ethoxydiethylaluminum was added to this toluene solution of borate at room temperature, and further hexane was added so that the borate concentration in the solution became 88 mmol / L. After that, the mixture was stirred at room temperature for 1 hour to obtain raw material (a-3), which is a reaction mixture containing borate.

[0111] (6) Preparation of solid catalyst component [A] While stirring a 1.04g / L hexane slurry of (A-3) carrier (Mg content concentration 8.0mmol / g) at 25℃, raw material (a-2) which is the titanium complex obtained in (4) above and raw material (a-3) which is the reaction mixture containing the borate obtained in (5) above were added simultaneously over 1 hour in amounts such that the titanium element in (a-2) and the boron element in (a-3) were 0.03 times the amount of Mg substance contained in the carrier, and the mixture was stirred for another 1 hour at the same temperature to react the titanium complex with the borate. After the reaction was completed, the supernatant was removed and the unreacted catalyst raw material was removed with hexane to obtain a solid catalyst component [A] in which catalytically active species were formed on the carrier.

[0112] [Production Example 2] (Solid catalyst component [B]) To 383 mL of hexane slurry containing 20 g of the (A-2) carrier synthesized in (2) of Production Example 1, 84 mL of 1.18 mol / L diethylaluminum chloride hexane solution was added over 1 hour while stirring at 60°C. After the addition, the reaction was continued at 65°C for 1 hour. After the reaction was completed, 200 mL of the supernatant was removed and the mixture was washed four times with 200 mL of hexane. Then, the solid catalyst component [B] was obtained under the same conditions as in (3) to (6) of Production Example 1.

[0113] [Production Example 3] (Solid catalyst component [C]) Average particle size is 10μm, surface area is 800m 2Spherical silica with a particle size of 1.9 mL / g and a particle pore volume of 1.9 mL / g was calcined at 600°C for 10 hours under a nitrogen atmosphere, followed by carbide vaporization and dehydration. The amount of surface hydroxyl groups of the dehydrated silica was 1.4 mmol / g per 1 g of SiO2. In a nitrogen atmosphere, 40 g of this dehydrated silica was dispersed in 800 mL of hexane in an autoclave with a capacity of 1.8 L to obtain a slurry. While keeping the obtained slurry at 50°C under stirring, 80 mL of a hexane solution of triethylaluminum (concentration 1 mol / L) was added, and then the mixture was stirred for 2 hours to react triethylaluminum with the surface hydroxyl groups of the silica, thereby obtaining a component [c-1] containing triethylaluminum-treated silica and a supernatant liquid, in which the surface hydroxyl groups of the triethylaluminum-treated silica were capped with triethylaluminum. Thereafter, the supernatant liquid in the obtained reaction mixture was removed by decantation to remove unreacted triethylaluminum in the supernatant liquid. Then, a suitable amount of hexane was added to obtain 880 mL of a hexane slurry of triethylaluminum-treated silica.

[0114] On the other hand, [(Nt-butylamido)(tetramethyl-η 5 200 mmol of [(-cyclopentadienyl)dimethylsilane)titanium-1,3-pentadiene (hereinafter referred to as "titanium complex") was dissolved in 1000 mL of Isopar E [a trade name of a hydrocarbon mixture manufactured by Exxon Chemical Company (USA)], and the titanium complex was dissolved in 1000 mL of AlMg6(C2H5)3(n-C4H9) which had been previously synthesized from triethylaluminum and dibutylmagnesium. 14 20 mL of a 1 mol / L hexane solution was added, and further hexane was added to adjust the titanium complex concentration to 0.1 mol / L to obtain component [c-2].

[0115] In addition, 5.7 g of bis(hydrogenated tallow alkyl)methylammonium-tris(pentafluorophenyl)(4-hydroxyphenyl)borate (hereinafter referred to as "borate") was added and dissolved in 50 mL of toluene to obtain a 100 mmol / L toluene solution of borate. 5 mL of a 1 mol / L hexane solution of ethoxydiethylaluminum was added to this toluene solution of borate at room temperature, and further hexane was added so that the borate concentration in the solution became 70 mmol / L. After that, the mixture was stirred at room temperature for 1 hour to obtain a reaction mixture [c-3] containing borate.

[0116] 46 mL of this reaction mixture [c-3] containing borate was added to 880 mL of the slurry of component [c-1] obtained above with stirring at 15 to 20°C to support the borate on the silica. After that, the supernatant liquid in the obtained reaction mixture was removed by decantation once with toluene and three times with hexane to remove excess borate.

[0117] 32 mL of the component [c-2] obtained above was added to the obtained borate-supported silica slurry, and the mixture was stirred for 3 hours to react the titanium complex with the borate. The supernatant liquid in the obtained reaction mixture was then removed by decantation to obtain a supported metallocene catalyst [C] in which catalytically active species were formed on the silica.

[0118] [Production Example 4] (Solid catalyst component [D]) 1,600 mL of hexane was added to an 8 L stainless steel autoclave purged with nitrogen. 800 mL of 1 mol / L titanium tetrachloride hexane solution and 1 mol / L AlMg6(C4H9) were added while stirring at 10°C. 12 800 mL of a hexane solution of an organomagnesium compound represented by (OSiBu2Et)5 was added simultaneously over 4 hours. After the addition, the temperature was slowly raised and the reaction was continued at 10°C for 1 hour. After the reaction was completed, 1,600 mL of the supernatant was removed and the solid catalyst component [D] was prepared by washing 10 times with 1,600 mL of hexane. The amount of titanium contained in 1 g of this solid catalyst component was 3.11 mmol.

[0119] Example 1 Hexane, ethylene, and catalyst were continuously fed into a 300 L vessel-type polymerization reactor equipped with a stirred device. The polymerization temperature was kept at 30° C. by jacket cooling. Hexane was fed from the bottom of the polymerization vessel at a rate of 80 L / Hr. Solid catalyst component [A] and triisobutylaluminum as a cocatalyst were used. Solid catalyst component [A] was added from the middle between the liquid level and the bottom of the polymerization vessel using two introduction lines, line 1 and line 2. The positions of the introduction lines were located on concentric circles at 0.3 times the cross-sectional radius from the center of the reactor for line 1 and 0.8 times the cross-sectional radius from the center of the reactor for line 2. Line 1 was added at a rate of 0.1 g / Hr and line 2 was added at a rate of 0.2 g / Hr. Triisobutylaluminum was added at a rate of 10 mmol / Hr from the liquid level and bottom of the polymerization vessel using an introduction line separate from the solid catalyst component [A]. Ethylene was fed from the bottom of the polymerization vessel to maintain the polymerization pressure at 0.5 MPa. The production rate of the ethylene polymer was 10 kg / Hr. The polymerization slurry was continuously discharged into a flash drum at a pressure of 0.05 MPa and a temperature of 65° C. so that the level of the polymerization reactor was kept constant, and unreacted ethylene was separated. The polymerization slurry was continuously sent to a centrifuge so that the level of the flash drum was kept constant, and the polymer was separated from the other solvents, etc. The temperature inside the centrifuge was kept at 75°C. The separated ethylene polymer was dried at 85°C for 4 hours while blowing with nitrogen to obtain ethylene polymer PE1.

[0120] The ethylene polymer PE1 obtained in Example 1 was measured according to the above-mentioned measurement method. (Physical property 1) Ratio of irreversible endothermic heat by step scan measurement (Physical property 2) Total content of Si and Al elements by SEM-EDX analysis of the compact obtained by press molding (Physical properties 3) Viscosity average molecular weight (Mv) (Physical Property 4) Mw / Mn (Physical Property 5) Melting endotherm (ΔH) by differential scanning calorimetry (DSC) Various physical properties were measured. In addition, various evaluations were performed, including (evaluation 1) tensile strength of the solid-state stretch-molded product, (evaluation 2) thickness unevenness of the solid-state stretch-molded product, and (evaluation 3) static antifouling property evaluation by immersion in actual seawater. The results are shown in Table 1.

[0121] Example 2 An ethylene polymer PE2 was obtained in the same manner as in Example 1, except that the solid catalyst component [B] was used as the catalyst. The physical properties and evaluation results of PE2 are shown in Table 1.

[0122] Example 3 An ethylene polymer PE3 was obtained in the same manner as in Example 1, except that the solid catalyst component [A] was used as the catalyst and the polymerization temperature was set to 55°C. The physical properties and evaluation results of PE3 are shown in Table 1.

[0123] Example 4 An ethylene polymer PE4 was obtained in the same manner as in Example 1, except that the solid catalyst component [A] was used as the catalyst and the centrifugation temperature was set to 88°C. The physical properties and evaluation results of PE4 are shown in Table 1.

[0124] Comparative Example 1 An ethylene polymer PE5 was obtained by the same procedure as in Example 1, except that the solid catalyst component [A] was used as a catalyst and the polymerization was carried out by adding the solid catalyst component [A] at a rate of 0.22 g / hour from one point of line 1 between the liquid level and the bottom of the polymerization vessel in the polymerization step. The physical properties and evaluation results of PE5 are shown in Table 1.

[0125] Comparative Example 2 The same procedure as in Example 1 was repeated except that the polymerization temperature was 75°C and the centrifugation temperature was 55°C, to obtain an ethylene polymer PE6. The physical properties and evaluation results of PE6 are shown in Table 1.

[0126] Comparative Example 3 An ethylene polymer PE7 was obtained in the same manner as in Example 1, except that the solid catalyst component [D] was used as the catalyst. The physical properties and evaluation results of PE7 are shown in Table 1.

[0127] Comparative Example 4 An ethylene polymer PE8 was obtained by the same procedure as in Example 1, except that in the polymerization step, MMAO-3A / hex (modified methylalumoxane, hexane solution containing 5.7% by mass of Al, manufactured by Tosoh Finechem Corporation) was added in an amount of 200 equivalents of the solid catalyst component [C], instead of the cocatalyst triisobutylaluminum. The physical properties and evaluation results of PE8 are shown in Table 1.

[0128] Comparative Example 5 An ethylene polymer PE9 of Comparative Example 5 was obtained in the same manner as in Example 1, except that the solid catalyst component [C] was used as the catalyst. The physical properties and evaluation results of the ethylene polymer PE9 are shown in Table 1.

[0129] Comparative Example 6 An ethylene polymer PE10 was obtained by the same operation as in Example 1, except that a solid catalyst component [C] was used as a catalyst, the solid catalyst component [C] was added at a rate of 0.22 g / hour from one point of line 1 between the liquid level and the bottom of the polymerization vessel in the polymerization step, the polymerization temperature was 75°C, and the centrifugation temperature was 50°C. The physical properties and evaluation results of PE10 are shown in Table 1.

[0130] [Table 1]

[0131] From the above results, the ethylene polymers of Examples 1 to 4 had excellent strength, and were highly rated in static antifouling properties when immersed in actual sea water. [Industrial Applicability]

[0132] The ethylene polymer of the present invention can be suitably used as a raw material for fibers that require high strength, or as a raw material for battery separators that require a uniform, thin, microporous membrane structure. The fibers obtained from the ethylene polymer of the present invention can be widely applied in industry to various products, such as high-performance textiles for various sportswear, bulletproof / protective clothing, protective gloves, various safety products, etc.; various rope products such as tag ropes, mooring ropes, yacht ropes, and construction ropes; various braided cord products such as fishing lines and blind cables; net products such as fishing nets and ball-proof nets; reinforcing materials for chemical filters and battery separators; various nonwoven fabrics, curtain materials for tents, etc.; sports products such as helmets and skis, speaker cones, prepregs, etc., and can provide these molded products with a long-term appearance retention due to their high antifouling properties, and long-term physical property stability with suppressed resin deterioration.

Claims

1. An ethylene polymer having a melting endotherm ΔH in differential scanning calorimetry of 190 J / g or more and 230 J / g or less, The irreversible endothermic heat (ΔH1) of the ethylene polymer obtained by the first scan measurement of the step-scan DSC; The ethylene polymer was annealed and melted in a step-scan apparatus at 155°C for 30 minutes, cooled to 50°C, and then measured again by step-scan DSC to obtain a non-reversible endothermic heat (ΔH2). The ratio of this to the non-reversible endothermic heat (ΔH2) was: (ΔH2) / (ΔH1)=0.1 or more and less than 0.6 The total content of Si and Al elements in a molded article according to the following <Condition (1)> and <Condition (2)> is 1.0 mass% or more and 6.0 mass% or less, as determined by SEM-EDX analysis. Ethylene polymer for thermoforming. <Condition (1)> 3 g of the ethylene polymer is pressed in a press molding machine at a maximum temperature of 130° C. and a pressure of 15 MPa for 10 minutes. <Condition (2)> Cool at 25° C. for 10 minutes while maintaining an average pressure of 11 MPa.

2. The viscosity average molecular weight is 1 million or more and 8.5 million or less. The ethylene polymer for thermoforming according to claim 1.

3. The molecular weight distribution (Mw / Mn) is 3.0 or more and 7.0 or less. The ethylene polymer for thermoforming according to claim 1 or 2.

4. The ethylene polymer for thermoforming according to any one of claims 1 to 3, which is for use in fibers.

5. A fiber comprising the ethylene polymer for thermoforming according to any one of claims 1 to 3.

Citation Information

Patent Citations

  • Net for preventing adhesion of marine organism

    JP1994261662A

  • Seawater corrosion resisting material for antisticking of marine living things

    JP1999001734A

  • Ultra high molecular weight polyethylene particle, method for producing the same and molded article by using the same

    JP2012025817A

  • Offshore Drilling or Production Vessel

    JP2015531330A

  • UHMWPE fiber

    JP2016524658A